Estrategias de marketing en tiempos de COVID 19 y el incremento de cartera de clientes en la empresa Zeaa Food Experience Riobamba. - Acurio Delgado, Andrés Sebastián (2023)
The following work entitled "Marketing strategies in times of covid 19 and the increase in the customer portfolio of the company zeaa food experience Riobamba" was carried out to establish objectives that would come to a solution to the main problem and thus determine how they affect marketing strategies in the increase of the client portfolio in the company zeaa food experience. For data collection, several bibliographical sources were used in order to study the variables which were the aim on this study. The methodology applied was the hypothetical – deductive, where the problem was identified by observing the phenomenon to be studied, while the type of inquiry was based on descriptive research. For the design, non-experimental analysis was carried out, because no variables were manipulated. Hence, it was necessary to work with the total population whose number is below 100 and therefore the sample was not calculated. In order to obtain the necessary information, the survey was used with a questionnaire that was obtained from the Zeaa Food Experience clients. The databases used for data collection were Microsoft Excel and SPSS. In the section of the statistical tables and the graphs that are displayed, their respective analysis and interpretation were carried out, after which the hypothesis was verified by means of the Chi-Square test, thus seeing that the alternate hypothesis is accepted and the null hypothesis is rejected. Once all the pertinent data was compiled, the conclusions and recommendations were given and it has been seen as important to make an improvement proposal that allows the company to increase its customer base.